Analysis of Risk Factors in Arterial Hypertension - Jalilova Umida Dzhumaevna (American Journal of Biomedicine and Pharmacy, 2024)
The number of cardiovascular diseases is increasing worldwide, and 1/3 of the deaths were recorded in 2019. The number of deaths increased from 12.1 million in 1990 to 18.6 million in 2019. (American College of Cardiology, 2020) Factors that increase the risk or "risk factors" for cardiovascular disease can be effectively controlled or their effects reversed. The data presented in the article is the result of an anonymous survey of patients diagnosed with arterial hypertension, during which an analysis of the socio-medical significance of the main risk factors in these patients was carried out.